Building a systematic model of risk and protective factors for intimate partner violence against women: the role of long-term community and structural disadvantages - Yakubovich, A (2019)
Background: Intimate partner violence (IPV) is estimated to affect at least 1 in 3 women, making it the most common form of violence perpetrated against women. While there is ample research studying IPV, there have been relatively few studies of patterns of risk over time and even less that have investigated the longitudinal relationship between IPV and community- or structural-level factors. Objectives: (1) Systematically summarise the longitudinal risk and protective factors for IPV against women; and, using data from the Avon Longitudinal Study of Parents and Children (ALSPAC) in the United Kingdom, evaluate: (2) the measurement and prevalence of IPV; (3) the dynamic relationship between objective and perceived measures of neighbourhood environments, and (4) the effect of long term exposure to neighbourhood-level deprivation on the risk of experiencing IPV among women. Method: This thesis used a variety of quantitative methods, including: a systematic, meta- analytic review; psychometric analysis; trajectory analysis; and marginal structural models using inverse probability weighting. I reviewed all available prospective-longitudinal studies of at least one risk or protective factor for IPV against women. My remaining empirical work used ALSPAC data from mothers and their children enrolled from birth between 1991-1992. When enrolled children were aged 21, they responded to a novel 8-item scale of physical, psychological, and sexual IPV experiences. Additionally, 18 years of data on neighbourhood environments, including the Indices of Multiple Deprivation, and family-level characteristics were available. Results: Few prospective-longitudinal studies on IPV against women have been conducted outside the United States or that investigated any community- or structural-level risk or protective factors. Among women participating in ALSPAC for 21 years, 32% had experienced IPV between ages 18-21 alone, with variations in their exposure to neighbourhood-level deprivation over the study period – demonstrating the need for further etiological study using appropriate longitudinal methods. Accounting for time- varying socioeconomic characteristics and sample attrition, I found that long-term exposure to more versus less deprived neighbourhoods over the first 18 years of life was associated with experiencing more frequent IPV and a higher risk of experiencing any IPV in early adulthood among participating women. Conclusions: This thesis synthesised, for the first time, the longitudinal literature on the risk and protective factors for IPV against women and contributed both methodologically and substantively to a major evidence gap identified: the association between neighbourhood-level deprivation and IPV. My findings demonstrate that long-term neighbourhood disadvantages predict women's increased risk of experiencing IPV and the value of longitudinal epidemiologic methods in advancing our understanding of IPV and its potential causes.